Advancing Ethiopia’s agricultural transformation: A consultative workshop on developing the National agroecology strategy - Balcha, Yodit; Degefie, Tibebe; Adimassu, Zenebe; Mockshell, Jonathan; Endalkachew, Wolde-Meskel (2024)
As part of the Private Sector Incentives and Investments project (PSii), activities under the Agroecological TRANSITIONS program are being implemented in Ethiopia by the Alliance of Bioversity International and CIAT. The PSii project team presented and showcased the need for the development of Ethiopia's National Agroecology Strategy (NAES) through their participation in the consultative workshop organized by the Ministry of Agriculture on November 26th, 2024 in Addis Ababa.